Evaluation Model of E-Learning Quality (Case Study: Payam Noor University of Arak) - Ranjkesh Rodsari, Mahboubeh; Fazallahi Qomshi, Seyfallah; Jafari, Seyyed Mohammad Bagher (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The objective was to propose a quality evaluation model for the e-learning system at Payam Noor University of Arak. Methods and Materials: The research method was applied in terms of objective and employed a mixed qualitative–quantitative data collection approach. In the qualitative section, after reviewing the literature and prior studies and formulating a preliminary conceptual model, the model was completed through semi-structured interviews with experts using thematic analysis or grounded theory. After the identified components were validated by experts through the Delphi method, the quantitative section proceeded with a descriptive-survey method to test the model’s fit. The qualitative study population consisted of e-learning experts, from which 12 individuals were selected using the non-random snowball sampling method until theoretical saturation was achieved. The quantitative study population consisted of 274 graduates of Payam Noor University of Arak who had received electronic instruction and were selected through simple random sampling. The data collection tool in the quantitative phase was a researcher-made questionnaire with 44 items. To assess reliability, Cronbach’s alpha, rho-A, composite reliability (CR), and Average Variance Extracted (AVE) as an indicator of convergent validity were used. The critical value for the reliability indices was set at 0.7 and for convergent validity at 0.5. Data analysis involved using the Kappa coefficient in the qualitative phase, and structural equation modeling (SEM) in the quantitative phase. The GOF index was applied to evaluate model efficiency using SPSS and PLS3 software. Findings: The results indicated that the main dimensions of quality included four categories: behavioral capability, academic capability, cognitive capability, and virtual learning experience. Additionally, six factors—cultural, pedagogical, learner-related, communicational, infrastructural, and institutional—were identified as determinants of the quality of the e-learning system at Payam Noor University. Therefore, the university can achieve four key outcomes—competitiveness, employability, economic benefits, and reputation—by establishing a high-quality educational system with the identified characteristics. Conclusion: It can be concluded that the quality evaluation model of e-learning at Payam Noor University follows a process-oriented approach in which factors, quality indicators, and outcomes are examined and assessed. This process will succeed in achieving its objectives only when it not only transforms the learner but also provides them with a valuable virtual learning experience; and, in terms of outcomes, all stakeholders within the higher education ecosystem will benefit from a valuable e-learning system.